2013
DOI: 10.1227/01.neu.0000431483.10031.89
|View full text |Cite
|
Sign up to set email alerts
|

Inhibition of c-Jun N-Terminal Kinase Activity Enhances Vestibular Schwannoma Cell Sensitivity to Gamma Irradiation

Abstract: Background Radiosurgery is increasingly used to treat vestibular schwannomas (VSs). Increasing the sensitivity of VS cells to irradiation (IR) could allow for lower and/or more effective doses of IR, improving safety and efficacy. Persistent JNK activity in VS cells reduces cell death by suppressing accumulation of reactive oxygen species (ROS) raising the possibility that JNK activity protects against IR-induced VS cell death, which is mediated by ROS. Objective Determine the extent to which JNK signaling c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
20
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 15 publications
(21 citation statements)
references
References 70 publications
1
20
0
Order By: Relevance
“…JNK is involved in cellular differentiation and proliferation, neurodegeneration, inflammatory conditions and apoptosis mediated by activation protein-1 (AP-1), RANTES, IL-8 and gm-CSF (23). Yue et al reported that inhibition of JNK activity can enhance the radiosensitivity of vestibular schwannoma cells (5).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…JNK is involved in cellular differentiation and proliferation, neurodegeneration, inflammatory conditions and apoptosis mediated by activation protein-1 (AP-1), RANTES, IL-8 and gm-CSF (23). Yue et al reported that inhibition of JNK activity can enhance the radiosensitivity of vestibular schwannoma cells (5).…”
Section: Discussionmentioning
confidence: 99%
“…JNK also participates in the phosphorylation of H2AX after radiation (4). Based on this finding, Yue et al reported that inhibition of JNK activity enhanced radiosensitivity and apoptosis in vestibular schwannoma (5). Accumulating evidence has demonstrated the important role of JNK in the process of DNA repair after radiation.…”
Section: Introductionmentioning
confidence: 97%
“…The results showed that, although all three signaling molecules were activated under irradiation, only JNK became more active after the addition of Tanshinone IIA (Figure A), suggesting that Tanshinone IIA enhanced the irradiation sensitivity via the JNK pathway. SP600125 (1,9‐pyrazoloanthrone anthrapyrazolone) was reported to be a specific inhibitor of JNK . Therefore, we next examined the survival and proliferation of laryngeal cancer cell AMC‐HN‐8 treated with irradiation, Tanshinone IIA, and SP600125 by clonogenic assay kit.…”
Section: Resultsmentioning
confidence: 99%
“…SP600125 (1,9-pyrazoloanthrone anthrapyrazolone) was reported to be a specific inhibitor of JNK. 1,[14][15][16] Therefore, we next examined the survival and proliferation of laryngeal cancer cell AMC-HN-8 treated with irradiation, Tanshinone IIA, and SP600125 by clonogenic assay kit. SP600125 treatment antagonized radiation sensitization induced by Tanshinone IIA (Figure 5B), confirming that Tanshinone IIA radiation sensitization was mediated by the JNK signaling pathway.…”
Section: Jnk Inhibitor Eliminates the Irradiation Sensitization Indmentioning
confidence: 99%
“…There are many reports that merlin inhibits several intracellular signals implicated in cell proliferation and tumor formation (1Y4). It was also reported that c-JUN N-terminal kinase activity could either promote tumor cell proliferation in VS or increase apoptosis in normal Schwann cells (17,18).…”
Section: Discussionmentioning
confidence: 96%